Advances in Materials and Technologies for Gas Sensing from Environmental and Food Monitoring to Breath Analysis. (22nd November 2022) - Milone, Angelo; Monteduro, Anna Grazia; Rizzato, Silvia; Leo, Angelo; Di Natale, Corrado; Kim, Sang Sub; Maruccio, Giuseppe
Abstract: Gas sensing research experiences a worldwide revival in the last years. From one side, the emergence of novel sensing materials enables unprecedented capacities for improving the device performances. From the other, the increasing opportunities for applications impacting current societal priorities highly motivate further studies. Herein, this field is reviewed with special attention to the emerging approaches and the most recent breakthroughs, challenges, and perspectives. In particular, this study focuses on: 1) the sensing layers analyzing recent trends toward nanostructured, low‐dimensional and composite materials; and 2) the latest achievements and targets in terms of applications, from environmental monitoring to food aroma identification and quality control up to the healthcare sector with breath analysis and diseases diagnosis. Abstract : Gas sensing research experiences a worldwide revival with the emergence of novel materials increasing opportunities for applications. Here, this study reviews: 1) the sensing layers analyzing recent trends toward nanostructured, low‐dimensional, and composite materials; and 2) the latest achievements and targets in terms of applications, from environmental monitoring to food aroma identification and quality control up to volatilomics and the healthcare sector.